2003
DOI: 10.1152/jn.00580.2002
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Classes of Cat Primary Visual Cortical Neurons In Vivo as Revealed by Quantitative Analyses

Abstract: To facilitate the characterization of cortical neuronal function, the responses of cells in cat area 17 to intracellular injection of current pulses were quantitatively analyzed. A variety of response variables were used to separate the cells into subtypes using cluster analysis. Four main classes of neurons could be clearly distinguished: regular spiking (RS), fast spiking (FS), intrinsic bursting (IB), and chattering (CH). Each of these contained significant subclasses. RS neurons were characterized by train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

55
406
3
28

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(492 citation statements)
references
References 100 publications
(114 reference statements)
55
406
3
28
Order By: Relevance
“…Furthermore, the action potential amplitude and width generated by the theta neuron are largely independent of the injected current amplitude. It is important to note that these intrinsic properties to a large extent have been observed in real cortical neurons in vitro and in vivo (McCormick et al 1985,Nowak et al 2003.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, the action potential amplitude and width generated by the theta neuron are largely independent of the injected current amplitude. It is important to note that these intrinsic properties to a large extent have been observed in real cortical neurons in vitro and in vivo (McCormick et al 1985,Nowak et al 2003.…”
Section: Introductionmentioning
confidence: 89%
“…The neurons spatially closest to each other are grouped together as a cluster. The analysis was performed using Ward's method which is based on the sum of squares between the clusters (Euclidean distances, summed over all variables) (Anderson et al, 1998) allowing an objective segregation of cell groups as previously reported (Pennartz et al, 1998, Cauli et al, 2000, Nowak et al, 2003. Electrophysiological variables were normalized to a common range (0-1) before performing the multidimentional analysis.…”
Section: Cluster Analysis Of Neuronal Subtypesmentioning
confidence: 99%
“…This manuscript focuses on the diversity of slow firing neurons of the MS/DB region. Analysis of the firing properties of other medial septal neuronal groups will follow in subsequent work.One major obstacle in categorizing neurons is determining whether a subjectively defined category can be assigned to a distinct subgroup or if a continuous spectrum of physiological properties exists in a larger population (for review see Nowak et al, 2003). In order to address this problem, we used cluster analysis on patch-clamp data recorded in vitro from adult rat MS/ DB neurons to identify subgroups of slow firing neurons.…”
mentioning
confidence: 99%
See 2 more Smart Citations